Tetralogy of Fallot with Sepsis Induced Coagulopathy in Case of Spontaneous Intracerebral Haemorrhage & Subarachnoid Haemorrhage - Emas, Bagas; Winarso, Achmad Wahib Wahju; Bisri, Dewi Yulianti (Jurnal Neuroanestesi Indonesia, 2024)
Congenital heart disease is the most common cause of stroke in some children. A child aged 5 years 9 months came with complaints of decreased consciousness and shortness of breath, weight 23 kg and height 140 cm, blood pressure 140/95 mmHg, pulse 52x/minute, axillary temperature 36.7oC, respiratory rate 44x/minute and obtained SpO2 62%78% using a nasal cannula. The patient was diagnosed with Tetralogy of Fallot through echocardiography but it was not corrected, Intracerebral Haemorrhage & Subarachnoid Haemorrhage were discovered on a CT scan, and sepsis induced coagulopathy through other supporting examinations. Children with congenital heart disease (CHD) are more susceptible to infection, this occurs because there is an increased risk for children with congenital heart disease to experience severe complications due to common infections such as sepsis. Sepsis itself will cause a coagulopathy disorder called sepsis induced coagulopathy (SIC) whose mechanism is also based on sepsis. Each of tetralogy of Fallot and Sepsis induced coagulopathy have mutually supporting roles in the mechanism of intracerebral haemorrhage. Most ICHs are caused by hypertension, arteriovenous malformation (AVM), and aneurysm. The patient experiences left ventricular dilatation, this can cause a long-term condition of hypertension. Through the SIC mechanism it can cause systemic inflammation and vascular injury caused by mass production of inflammatory cytokines and their release into the circulation causing excessive activation of the clotting process, impaired fibrinolysis, and suppression of anticoagulant mechanisms which can cause endothelial dysfunction and thrombus formation.